2017
DOI: 10.1308/rcsann.2017.0105
|View full text |Cite
|
Sign up to set email alerts
|

Adult Burkitt’s lymphoma presenting as intussusception: first UK case report

Abstract: Colonic intussusception is rare in adults and can present with non-specific symptoms that can make diagnosis difficult and delayed. Unlike in children, it is commonly due to a pathological lead point that is often malignant. This case is the first reported case of adult intussusception due to Burkitt's lymphoma in the UK. We describe the case of a 22-year-old woman who presented with 4-week history of intermittent epigastric pain. On the third hospital admission, the diagnosis was made by abdominal computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…In fact, up to date, less than 20 cases have been reported in adults. Simson et al 4 , in 2017, reported the first case in the United Kingdom of a 22-year-old patient whose diagnose was performed through a CT scan of the abdomen and was later derived to surgical management. Reports have also been carried out in Turkey 5 , Portugal 6 and Korea 7 , among others, but so far none has been described in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, up to date, less than 20 cases have been reported in adults. Simson et al 4 , in 2017, reported the first case in the United Kingdom of a 22-year-old patient whose diagnose was performed through a CT scan of the abdomen and was later derived to surgical management. Reports have also been carried out in Turkey 5 , Portugal 6 and Korea 7 , among others, but so far none has been described in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic BL attacks regions outside Africa, and majority of cases occur in the United States (US) and Western Europe. Sporadic BL frequently involves distal ileum, caecum and mesentery, presenting symptoms include abdominal swelling due or pelvic mass, abdominal pain and intussusception-related symptoms of bowel obstruction [8]. Intussusception in itself is a very rare presentation of BL.…”
Section: Discussionmentioning
confidence: 99%
“…Burkitt´s lymphoma is a highly aggressive malignancy usually affecting children and young adults. In more elderly population its incidence is low, with patients 20-30 years of age showing a figure of 0.6 per million [ 4 ]. The first reported case of BL was observed in young children from Africa by Burkitt in 1958.…”
Section: Discussionmentioning
confidence: 99%